KORELASI ASPEK IBU TERHADAP KETIDAKLENGKAPAN IMUNISASI DASAR PADA BALITA - Novika, Revi Gama Hatta; L.Tobing, Hendri Parluhutan; Pratami, Intan Monik; Purwadi, Happy Novriyanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Incomplete immunization can lead to a decrease in the immune system in toddlers, making them more susceptible to various infections. Maternal education, knowledge and occupation factors have a significant influence on the completeness of basic immunization in children. The purpose of the study was to determine the correlation of maternal aspects to the incompleteness of basic immunization in toddlers. The research design used in this study was Cross Sectional. The research was conducted in Wonosari Village. The research was conducted in November 2023. The study population was mothers who had babies aged 9-12 months in Wonosari Village as many as 147 babies. The sample amounted to 102 babies. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between maternal employment (p value: 0.021) and no relationship between maternal knowledge (p value: 0.449) to the completeness of basic immunization. It is recommended that mothers bring their babies for basic immunization or vaccines so that babies and children can avoid a disease that can be prevented by basic immunization, so that they have high immunity.Keywords: Immunization, Maternal Education, Maternal Knowledge.